2022
DOI: 10.31557/apjcb.2022.7.1.15-20
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact on Survival of Early Relapse after Autologous Stem Cell Transplantation with Non-cryopreserved Stem Cells for Multiple Myeloma in Real Life: A Single-center Cohort Study from Oran (Algeria)

Abstract: Background: The aim of this retrospective study was to analyze early relapse in multiple myeloma (MM) in real life and to evaluate its impact on overall survival (OS) and progression-free survival (PFS). Methods: Two groups of patients were identified according to the date of occurrence of relapse after autologous transplantation, within less than 24 months, defining early relapse (G1), or after more than 24 months, defining late relapse (G2). Results: A total of 307 patients with MM were enrolled, including 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the absence of risk-adapted, MRD-directed risk stratification treatment, HSCT, and immunotherapy, our study found that patients with relapsed AML had a poor prognosis. As a result, we believe that MRD-directed risk stratification treatment, HSCT, and immunotherapy might be beneficial to individuals with relapsed AML (Bekadja et al, 2022). Moreover, patients with late relapse, who had a better survival outcome than those who relapsed earlier, should receive intensive re-induction chemotherapy to achieve CR2 and strategies should be developed to assist healthcare providers to persuade these patients and their families to accept this life-prolonging treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of risk-adapted, MRD-directed risk stratification treatment, HSCT, and immunotherapy, our study found that patients with relapsed AML had a poor prognosis. As a result, we believe that MRD-directed risk stratification treatment, HSCT, and immunotherapy might be beneficial to individuals with relapsed AML (Bekadja et al, 2022). Moreover, patients with late relapse, who had a better survival outcome than those who relapsed earlier, should receive intensive re-induction chemotherapy to achieve CR2 and strategies should be developed to assist healthcare providers to persuade these patients and their families to accept this life-prolonging treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Till now there are different staging methods have been introduced and some became applicable in clinic or laboratories, for instance Mohammad et al, (2019) introduced staging based on Beta2 microblubolin, percentage of bone marrow plasmacells, serum free light chaing (FLC), serum protein electrophoresis, and serum and urine immunofixation, by this approche the biochemical staging of the MM introduced three stages Mohammad et al, (2019), by the way some researches have been established the predictive or prognostic factors (Bekadja et al, 2022) based on clinical or biochemical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a treatable but incurable cancer. High expression of abnormal M protein in blood and urine will accumulate and result in organ dysfunction such as bone damage and kidney problems, then the patient becomes symptomatic (Khalife et al, 2021;Bekadja et al, 2022).…”
Section: Introductionmentioning
confidence: 99%